Instructional Strategies of Teachers, Reading Proficiency, and Reading Motivation of Grade 7 Students - Raquel B. Conel; Lehai B. Beloro (International Journal of Multidisciplinary: Applied Business and Education Research, 2026)
This study determined the commonly used instructional strategies and the relationship of reading motivation on the reading proficiency levels of Grade 7 students, and used these findings as basis for developing a teacher-led intervention material. The research design used was descriptive-correlational design with a sample of 139 Grade 7 students and 7 English teachers. Analysis of data was done using Weighted Mean, Pearson Product Moment Correlation Coefficient, Coefficient of Determination and modified ADDIE model. Results showed that the identified instructional strategies were used often by teachers, their average weighted mean (AWM) being 3.09. Regarding reading skills, students displayed strong reading fluency (56.80%) and moderate vocabulary knowledge (59.70%). Nevertheless, students showed a frustration-level performance in reading comprehension (43.90%), indicating that they struggle to independently understand texts and need significant support from teachers to grasp reading materials. Analysis of reading motivation of Grade 7 showed that the level of motivation was moderately high, with an (AWM) of 2.91. Correlation tests revealed that reading motivation had a very weak effects on reading proficiency, with r-squared values ranging from 0.0016% to 2.7556%, suggesting minimal contribution of motivation to students’ reading performance. These results were the foundation of a teacher-directed intervention resource aimed at overcoming the challenges outlined and helping the students to become more proficient and motivated in reading. Altogether, the research highlights the necessity of more specific and teacher-centered strategies to enhance the level of reading comprehension and interest among the students.